Analysis of Potential Financial Distress Using the Altman Method (Z-Score), Springate Method (S-Score), and Zmijewski Method (X-Score) in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2019-2022 - Adella; Winanti; Mega Indri Nurwati; Fida Maulida Natswa; Ilham Sidiq; Fajar Riyanto; Istajib Kulla Himmyázz (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
This study aims to find out whether there is a score difference between Altman, Springate, and Zmijewski's methods in predicting Financial Distress, as well as to find out which prediction model is the most accurate in predicting Financial Distress in manufacturing companies in the food & beverage subsector. The data used in this study is the company's financial statements published on the Indonesia Stock Exchange. The sample in this study is 6 food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique using nonprobability sampling is purposive sampling. This study compares the scores of three financial distress prediction models using the accuracy of the prediction model by considering the level of accuracy and type of error. The results of this study show that there is a difference between the three prediction models. Zmijewski's model is the best with an accuracy rate of 1% and an error type of 0%, the second is the springate model with an accuracy rate of 0.958% and an error type of 0.041%, and the last is the Altman model with an accuracy rate of 0.083% and an error type of 0.916%.